Opportunities for economic revitalization through inter-industrial relationships: The case of blue economy - Sousa, C.; Fontes, M.; Conceição, O. (Proceedings of the 16th European Conference on Innovation and Entrepreneurship (ECIE 2021), 2021)
This paper proposes that collaborative relationships in the context of research and innovation projects can be a first step towards the development of new products or adaptation to new markets that may drive diversification processes in established/mature sectors; and that technology-based firms can play a key role in these processes, as intermediaries and co-innovators.-economic development and sustainability in the conduction of human activities related with the ocean. Transformative activities in this field are especially important, given the weight of ocean-related traditional sectors in the economic activity of several European countries. The paper maps the interactions between new and established Portuguese industries, to investigate whether and to extent inter-sectoral relationships are leading to the development of innovative and sustainable solutions, as well as which sectors have a more determinant role. Then it looks for evidence of revitalization and transformation processes being induced by collaboration with firms from new industries. Implications for transformative innovation policies are derived.